2014
DOI: 10.1136/bmjspcare-2013-000565
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ attitudes towards prescribing opioids for refractory dyspnoea: a single-centred study

Abstract: This group of doctors was aware of the use of opioids for refractory dyspnoea and reported a willingness to prescribe opioids for this symptom. However, confidence varied considerably depending on clinical context. Fears about side effects were prevalent and should be addressed. Doctors would benefit from clearer guidance on prescribing regimes, specifically in circumstances other than the dying patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 15 publications
2
32
0
2
Order By: Relevance
“…This is comparable to the Dutch survey in which 20% of doctors were worried about opioid induced respiratory depression . Meanwhile other small studies, including qualitative data, have reported concern regarding respiratory depression to be much higher, nearer 56–62% of doctors surveyed . However, to date there have been no cases in the medical literature of respiratory depression from low dose opioids for the treatment of refractory breathlessness.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This is comparable to the Dutch survey in which 20% of doctors were worried about opioid induced respiratory depression . Meanwhile other small studies, including qualitative data, have reported concern regarding respiratory depression to be much higher, nearer 56–62% of doctors surveyed . However, to date there have been no cases in the medical literature of respiratory depression from low dose opioids for the treatment of refractory breathlessness.…”
Section: Discussionsupporting
confidence: 66%
“…Despite Australian and international COPD guidelines now recommending opioids to palliate breathlessness in advanced disease, this distressing symptom remains undertreated, with lack of clinician knowledge or experience being a well‐recognised barrier to opioid prescription . Junior hospital doctors are at the ‘front line’ of tertiary medical care and therefore commonly manage, under consultant supervision, COPD patients with severe breathlessness.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids are recommended by multiple evidence-based guidelines for the relief of dyspnea (26)(27)(28). This finding may suggest that primary care doctors or pulmonologists lack the training and expertise for identifying who would benefit from opioids and anxiolytics and how to appropriately prescribe and monitor their effects (29,30). A palliative care physician may be less reluctant to initiate these medications and be better equipped for monitoring effectiveness and side effects.…”
Section: Uncontrolled Symptomsmentioning
confidence: 99%
“…Although systemic opioids are a safe and effective intervention for the management of dyspnea in cardiopulmonary disease (1, 29, 60), many healthcare providers remain skeptical of their use for fear of adverse side effects (22,59,79). In theory, intrapulmonary mu-opioid receptors (12,17,18,34,81) represent a promising pharmacological target in the management of dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, inhaled opioids are attractive because this route of opioid administration is the most accepted/preferred among patients with dyspnea (67) and may be associated with no adverse side effects (8) that have limited the widespread use of systemic opioids for relief of dyspnea (22,59,79). Nevertheless, only one randomized controlled trial has examined the effect of nebulized morphine (2.5 and 5.0 mg) on exertional dyspnea and incremental cycle exercise capacity in six patients with RLD: three with pulmonary fibrosis; two with scleroderma; and one with sarcoidosis (24).…”
mentioning
confidence: 99%